2011
DOI: 10.1038/jid.2010.331
|View full text |Cite
|
Sign up to set email alerts
|

A Flexible Multiplex Bead-Based Assay for Detecting Germline CDKN2A and CDK4 Variants in Melanoma-Prone Kindreds

Abstract: Background The presence of recurrent high-risk mutations in CDKN2A and CDK4 among melanoma-prone kindreds suggests that a high-throughput, multiplex assay could serve as an effective initial screening tool. Moreover, with the emergence of new melanoma risk single nucleotide polymorphisms (SNPs) through genome-wide association studies, a flexible platform that can easily accommodate these new risk alleles is needed for more accurate genetic risk profiling. To this end, we have developed a novel melanoma-associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 17 publications
(23 reference statements)
0
10
0
Order By: Relevance
“…7, 8, 9 DNA was extracted from peripheral blood leucocytes and subjected to the same mutational analysis as listed above. Statistical analyses were performed with SigmaStat.…”
Section: Methodsmentioning
confidence: 99%
“…7, 8, 9 DNA was extracted from peripheral blood leucocytes and subjected to the same mutational analysis as listed above. Statistical analyses were performed with SigmaStat.…”
Section: Methodsmentioning
confidence: 99%
“…Some scholars found, at DNA level, these two genes simultaneously or at least one of their downstream target objects changed in malignant melanoma cell lines (Walker et al, 1998). CDKN2A gene transcripts can inhibit CDK4 (Lang et al, 2011) and stabilize the p53 gene (Huschtscha et al, 2009); CDKN2B can inhibit the activity of CDK4 and CDK6 and stimulate cells' passing-through of G1/S check point and replication (Soto et al, 2005). The down-regulation of CDKN2A and CDKN2B in metastasis group of this study was probably through decreasing the inhibition of CDKs, which pushed cell cycle to pass G1/S monitoring point, resulting in rapid growth and uncontrolled proliferation of tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to realize though that certain driver mutations in cancer development are hereditary. As an example, the CDK4 mutation that results in a novel HLA-A2-restricted T-cell epitope (Wolfel et al, 1995) may seem a perfect target for TCR gene therapy but is sometimes observed in familial melanoma (Lang et al, 2011). For these patients, the targeting of this antigen would certainly not result in selective tumor cell recognition.…”
Section: Which Antigens To Pick: Safety Concernsmentioning
confidence: 98%